Factors affecting the performance of community health workers in India: a multi-stakeholder perspective - Reetu Sharma; Premila Webster; Sanghita Bhattacharyya (Taylor & Francis Group, 2014)
Background: Community health workers (CHWs) form a vital link between the community and the health department in several countries. In India, since 2005 this role is largely being played by Accredited Social Health Activists (ASHAs), who are village-level female workers. Though ASHAs primarily work for the health department, in a model being tested in Rajasthan they support two government departments. Focusing on the ASHA in this new role as a link worker between two departments, this paper examines factors associated with her work performance from a multi-stakeholder perspective. Design: The study was done in 16 villages from two administrative blocks of Udaipur district in Rajasthan. The findings are based on 63 in-depth interviews with ASHAs, their co-workers and representatives from the two departments. The interviews were conducted using interview guides. An inductive approach with open coding was used for manual data analysis. Results: This study shows that an ASHA's motivation and performance are affected by a variety of factors that emerge from the complex context in which she works. These include various personal (e.g. education), professional (e.g. training, job security), and organisational (e.g. infrastructure) factors along with others that emerge from external work environment. The participants suggested various ways to address these challenges. Conclusion: In order to improve the performance of ASHAs, apart from taking corrective actions at the professional and organisational front on a priority basis, it is equally essential to promote cordial work relationships amongst ASHAs and other community-level workers from the two departments. This will also have a positive impact on community health.